2016
DOI: 10.1016/j.rppede.2016.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of extrinsic factors on fine motor performance of children attending day care

Abstract: Objective:To assess the impact of extrinsic factors on fine motor performance of children aged 2-years old.Methods:73 children attending public and 21 private day care centers were assessed. Day care environment was evaluated using the Infant/Toddler Environment Rating Scale-Revised Edition (ITERS-R), fine motor performance was assessed through the Bayley Scales of Infant and Toddler Development-III (BSITD-III), socioeconomic data, maternal education and time of start at the day care were collected through int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
(27 reference statements)
0
5
0
3
Order By: Relevance
“…In this context, we noticed that the mother's lower level of education was associated with impaired neuropsychomotor development only in the domain of fine adaptive motor skills. One study reported that a high maternal schooling is related to the children's fine motor performance 23 . Thus, we suggested that greater access to information is related to greater availability of toys and, consequently, to a better stimulation of fine motor skills.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, we noticed that the mother's lower level of education was associated with impaired neuropsychomotor development only in the domain of fine adaptive motor skills. One study reported that a high maternal schooling is related to the children's fine motor performance 23 . Thus, we suggested that greater access to information is related to greater availability of toys and, consequently, to a better stimulation of fine motor skills.…”
Section: Discussionmentioning
confidence: 99%
“…All these predictors need to be developed in the preschool period, since the experiences lived in these years are related to the cognitive and neuropsychomotor development and dependent on the quality of the stimuli received, which may come from both the family and the school environment 24 . Justifying, thus, the importance of early detection of changes in this period.…”
Section: Resultsmentioning
confidence: 99%
“…The development of motor skills is the development of coordinated physical movement control between nerve centers, nerves and muscles [17]. fine motorics is defined as movement performed by using smooth muscles such as drawing, cutting, and forming.…”
Section: B Fine Motoricmentioning
confidence: 99%